Management of non-absorbable mesh infection after hernia repair by negative pressure wound therapy (IMC Journal of Medical Science, 2019)
Background and objectives: Mesh infection following hernia repair has previously often resulted in removal of mesh. The aim of this study was to evaluate if negative pressure wound therapy (NPWT) can be used to treat such complications and preserve the mesh.Materials and method: A prospective study was carried in the Department of Surgery, BIRDEM General Hospital from January 2017 to January 2019. Patients with deep wound infection and exposed infected mesh after hernioplasty were included in the study. Patients’ demographics, existing comorbidities and outcome were recorded. All patients were treated with NPWT till the wound was covered with healthy granulation tissue and closed.Results: NPWT was used to treat 7 patients with mesh infection following hernia repair. There was 2 male and 5 female cases and age ranged from 38-58 years. With NPWT the mesh in 6 patients (86%) out of 7 could be completely salvaged and wound closed with secondary suturing. However, in 1 patient although the mesh covered with granulation tissue by NPWT and wound was closed; but it had to be partly removed later on due to development of chronic discharging sinus 20 days after stitch removal.Conclusion: The study demonstrated that NPWT was a useful technique for the treatment and preservation of infected mesh after hernia repair.IMC J Med Sci 2019; 13(1): 008